Homicides involving Black victims are less likely to be cleared in the United States - Campedelli, Gian Maria (Criminology, 2024)
Does a victim's race explain variation in the likelihood of homicide clearance? Attempts to address this issue date back to the 1970s. Yet, despite its theoretical and policy relevance, we lack a comprehensive and clear empirical answer to this critical question. Here, I causally focus on this problem by investigating racial disparity in homicide clearance in the United States, exploiting two sources covering the 1991-2020 period: the Murder Accountability Project data set (N = 522,278) and the National Incident-Based Reporting System data set (N = 98,677). I primarily analyze these sources by employing exact matching to achieve perfect covariate balance and subsequently isolate the effect of race on the probability of clearance. For comparative purposes, I also use regression adjustment without matching obtaining complementary estimates. I demonstrate that the likelihood of clearance is 3.4 to 4.8 percent lower for homicides involving Black victims, depending on the sampling and estimation approach. In addition, I empirically show that this race effect is slightly higher for males and that racial disparity has moderately but significantly increased over time. These findings contribute to the extensive amount of evidence on discrimination affecting Black individuals in the administration of justice in the United States, calling for structural efforts to reduce this divide.